Quality of Service in home network: VLAN zeroconfiguration network. (2nd August 2006) - La Corte, Aurelio; Sicari, Sabrina
The proliferation of devices together with the necessity of being constantly connected to the network is considered to cause the need for 'Autoconfiguration'. At the same time, it is necessary to guarantee an adequate level of quality of service. So, we propose to use together zeroconfiguration protocols and Virtual LANs.